Structure-free and dynamic-adaptive data fusion algorithm for wireless sensor networks - Jun YUE; Wei-ming ZHANG; Wei-dong XIAO; Da-quan TANG; Jiu-yang TANG (Tongxin xuebao)
Researches on the problem that the existing data fusion algorithms couldn't satisfy the new application re-quirements,ie,frequent dynamic change of network and hi demand with reliability of data communication,a struc-ture-free and dynamic-adaptive data fusion algorithm was presented which divided the network into several grids,sensors perform data communication according to grids and adopt many-to-many data communication manner,there was no need for sensors to establish and maintain a structure.The results of simulation experiments show that this algorithm is able to adapt the dynamic change of network and offer high reliable data communication while performs the task of data fusion.